Eleventh Five Year Plan (2007-2012) Volume-I Inclusive Growth - Planning Commission (Planning Commission, 2007)
India has entered the Eleventh Plan period with an impressive record of economic growth. After a lacklustre performance in the 9th Plan period (1997-98 to 2001-02), when GDP grew at only 5.5% per annum, the economy accelerated in the Tenth Plan period (2002-03 to 2006-07) to record an average growth of 7.6%, the highest in any Plan period so far. Besides, there was acceleration even within the Tenth Plan period and the growth rate in the last 4 years of the Plan has averaged 8.6% making India one of the fastest growing economies in the world.
Government of India
Government of India